An evaluation of compatibility of three different impression materials to three different tray acrylic materials using tray adhesives: An In vitro Study - C B Shanthana Lakshmi; B Umamaheswari; Achut R Devarhubli; Sushant Pai; Tejendra Nandakumar Wadambe (Wolters Kluwer Medknow Publications, 2018)
Background: Impressions are an integral part of prosthodontics. Elastomeric impression materials are the impressions materials of choice in fixed prosthodontics for its better surface detail reproduction. Out of the elastomers available, vinyl polysiloxane represents the state of art impression material in prosthodontics, but even these materials cannot give an accurate reproduction of the tissues if there is separation of impression materials from the tray which may results in a distorted impression leading to poor final restorations made from such impressions. Hence, tray adhesives need to be applied to the tray to obtain an accurate and consistent impression. The purpose of the study was to evaluate the compatibility of three different impression materials to three different tray acrylic materials using tray adhesive, by determining the tensile bond strength. Materials and Methods: Two acrylic discs were utilized to make one impression sample of 3 mm thickness. The dimension of each acrylic disc was 2 mm in thickness and 2 cm in diameter. Specimens were made using a standard stainless steel die of the above-mentioned dimensions. A total of 135 specimens were prepared which included 15 samples in each category of nine groups. The samples were subjected to tensile bond strength testing using the universal testing machine and the values were recorded. All the values were subjected for statistical analysis. Results: Impregum (3M) specimens had demonstrated the highest tensile bond strength value (51.60N). Statistical analysis was done using Tukey's post hoc test and one-way ANOVA. Highly Statistical significant results were evident in Impregum (3M) and Indentium, as the P = 0.00. Conclusion: In this study Impregum (3M), specimens had highest tensile bond strength values compared to the other Groups followed by Indentium.